Relationship between telomerase activity and its subunit expression and inhibitory effect of antisense hTR on pancreatic carcinoma - Zhou, Jia-Hua (World J Gastroenterol, 2003)
AIM: To directly investigate the relationship between telomerase activity and its subunit expression and the inhibitory effect of antisense hTR on pancreatic carcinogenesis. METHODS: We examined the telomerase activity and its subunit expression by cell culture, polymerase chain reaction (PCR), PCR-silver staining, PCR-ELISA, DNA sequencing, MTT and flow cytometry methods. RESULTS: PCR-silver staining and PCR-ELISA methods had the same specificity and sensitivity as the TRAP method. Telomerase activity was detected in the extract of the 10(th), 20(th)and 30(th) passages of P3 cells,while it was absent in fibroblasts. Furthermore, after the 30th generation, the proliferation period of fibroblast cells was significantly prolonged. Telomerase activity and hTERTmRNA were detected in two pancreatic carcinoma cell lines, but were found to be negative in human fibroblast cells. Telomerase activity and hTERTmRNA were tested in pancreatic carcinoma specimens of 24 cases. The telomerase activity was positive in 21 of the 24 cases (87.5%), and the hTERTmRNA in 20 cases (83.3%). In adjacent normal tissues positive rates were both 12.5%. There was a significant difference between the two groups. This indicated a significant correlation between the expression level of telomerase activity and histologic differentiation, metastasis and advanced clinical stage of pancreatic carcinoma. Our findings showed that the expressions of hTR and TP1mRNA were not correlated with the activity of telomerase but the expression of hTERTmRNA was. After treatment with PS-ODNs, telomerase activity in P(3) cells weakened and the inhibiting effect became stronger with an increase in PS-ODNs concentration. There was a significant difference between different PS-ODN groups (P < 0.05). Inhibition of telomerase activity occurred most significant with PS-ODN1.The results of the FCM test of pancreatic cancer P(3) cells showed an increase in the apoptotic rate with increasing PS-ODN1 and PS-ODN2 concentrations. CONCLUSION: The expression of telomerase activity has a significant relationship to carcinogenesis. A strong correlation exists between telomerase activity and hTERTmRNA expression. The up-regulation of hTERTmRNA expression may play a critical role in human carcinogenesis. The expression of telomerase activity and its subunit level in pancreatic carcinoma significantly correlate with the clinical stage of pancreatic carcinoma and hence, may be helpful in its diagnosis and prognosis. The anti-hTR complementary to the template region of hTR is sufficient to inhibit P3 cell telomerase activity and cell proliferation in vitro, and can lead to a profound induction of programmed cell death.